Healthcare Resource Utilization Among Patients With Agitation in Alzheimer Dementia - Christie Teigland; Zulkarnain Pulungan; David Bruhn; Steve Hwang (Journal of Health Economics and Outcomes Research)
**Background:** Agitation in Alzheimer dementia is common, but the associated healthcare burden remains unclear. **Objective:** This retrospective analysis evaluated baseline characteristics, healthcare resource utilization, and costs among patients with agitation in Alzheimer dementia and those without agitation in Alzheimer dementia. **Methods:** Medicare beneficiaries from 100% of the Medicare Fee-for-Service claims database (2009-2016) with 2 or more claims 30 or more days apart for both Alzheimer’s disease and dementia and continuous enrollment with medical/pharmacy coverage for 6 months before and 12 months after the index diagnosis were included. Patients with agitation in Alzheimer dementia were identified by 2 or more claims 14 or more days apart using _International Classification of Diseases-9-CM/-10-CM_ codes based on the provisional International Psychogeriatric Association agitation definition. Patients with severe psychiatric disorders were excluded. Two cohorts of patients (with and without agitation) were then defined, and patient characteristics, healthcare resource utilization, and costs were compared in a descriptive exploratory analysis. **Results:** Of 2 684 704 Fee-for-Service patients with Alzheimer dementia, 769 141 met all inclusion criteria; among these, 281 042 (36.5%) had agitation. The mean age in patients with and without agitation in Alzheimer dementia was 83 years. Most patients in both groups were female, but the proportion of males was slightly higher in the agitation in Alzheimer dementia group (30.3% vs 28.2%, respectively). Patients with agitation in Alzheimer dementia were more likely than those without agitation in Alzheimer dementia to have lower socioeconomic status (dual eligibility for Medicaid, 45.0% vs 41.7%, respectively) or be disabled (10.5% vs 9.4%). Overall, healthcare costs were higher in the agitation in Alzheimer dementia population compared with those without agitation in Alzheimer dementia (mean cost PPPY, $32 322 and $30 121, respectively), with the largest differences observed in inpatient and post-acute care costs. **Conclusions:** These exploratory findings underscore the substantial economic burden of agitation in Alzheimer dementia and highlight the need for treatment options for the agitation in Alzheimer dementia population to improve associated health outcomes.